The persian pickle club eaudiobook - Dallas, Sandra (Recorded Books Inc., 2010)
The best-selling author of Alice's Tulips and other popular novels, Sandra Dallas exhibits a well-honed talent for evoking the past. In The Persian Pickle Club, Dallas transports listeners to 1930s Kansas, where a club of quilters welcomes a new member-and then must turn to each other for support when a startling secret comes to light. "A colorful exploration of Depression-era Kansas and the meaning of friendship."-New York Times Book Review